Destination: demain - Barrieau, Pierre; Richard, Geneviève (Continuité, 2024)
Keywords: Transport en commun

L'histoire du chemin du Roy, XVIII-XXᵉ siècles : étude historique d'une route, d'un symbole, d'un récit - Fortin-Dupuis, Simon (Université Laval, 2024)
Keywords: Routes

Tramway à Montréal-1861 à 1959 - Tessier, Stéphane (Il était une fois...Montréal-Nord, 2024)
Keywords: Montreal Street Railway Company; Tramways

Saint-Louis-Du-Mile-End. De la campagne à la ville (Bulletin de la Société d'histoire et de généalogie du Plateau-Mont-Royal, 2023)
Keywords: Chemins de fer; Institution des sourds-muets; Logement; Mile End; Soeurs de la Providence

DAWSON, ARTHUR OSBORNE - Miller, Carman (Dictionnaire biographique du Canada, 2023)

MUIR, HENRIETTA LOUISE - Roome, Patricia (Dictionnaire biographique du Canada, 2023)

Une mesure d'origine britannique. Les barrières à péage à Outremont - Waché, Gabriel; Bizier, Hélène-Andrée (Mémoire vivante, 2023)
Keywords: Outremont; Routes

“Far From Uninteresting”: Getting to Know the St. Lawrence River at Montreal During the Construction of the Victoria Bridge - Braiden, Heather (Urban History Review/Revue d'histoire urbaine, 2022)
In northern cities like Montreal, Quebec, Canada, the winters are long, and the construction season is condensed. In the mid-nineteenth century, knowing the St. Lawrence River’s seasonal variations and local construction customs helped railway and bridge builders save time and frustration during the very short working seasons. In this article, I investigate how technical and quasi-technical communications generated during the construction of the Victoria Bridge (1854–1860) are a rich source of urban knowledge. By examining visual and textual evidence in The Construction of the Great Victoria Bridge in Canada, I demonstrate how representations of the construction process are a tangible medium through which practical experience and a personal way of knowing the urban landscape are mediated. I argue that everyday experience and tacit knowledge move between social worlds and inform how audiences know and understand the colonial city.
Keywords: Victoria (pont)

La Petite-Bourgone: bercail de l'industrie et quartier historique multiracial de Montréal - High, Steven (Bulletin de l'AQPI, 2022)
Keywords: Anglophones; Canadien National; Francophones; Grand Tronc; Lachine (canal); Montreal Rolling Mills; Noirs; Petite-Bourgogne; Quartiers; Sainte-Cunégonde

DUPUIS, JOSEPH-NARCISSE (Dictionnaire biographique du Canada, 2022)

Railways and the Urban Soundscape: Montreal, 1850s-1950s - Rudy, Jarrett; Fahrni, Magda; Kenny, Nicolas (Urban History Review / Revue d'histoire urbaine, 2022)
Keywords: Chemins de fer; Paysages

Le boulevard Saint-Laurent et son histoire - Tessier, Stéphane (Il était un fois... Montréal Nord, 2022)
Keywords: Routes; Saint-Laurent (rue)

BÉÏQUE, FRÉDÉRIC-LIGORI - Vallières, Marc (Dictionnaire biographique du Canada, 2022)

Building landscape narratives: the material and visual culture of bridge construction in Montreal, 1854-1930 - Braiden, Heather (Université McGill, 2021)
Keywords: Ponts; Victoria (pont)

À la croisée des chemins : mise en place et implantation du réseau de télégraphe électrique canadien, 1846-1867 - Dumais-Gingras, Pierre (Université du Québec à Montréal, 2021)
Keywords: Téléphone

Au croisement de la perte de mémoire et de la créativité communautaire: de nouvelles innovations dans les anciens ateliers ferroviaires de Pointe-Saint-Charles - Elliott, Andrew (Bulletin de l'AQPI, 2021)
Keywords: Canadien National; Chemins de fer; Conservation; Grand Tronc; Patrimoine

“The Severity of This Service…” Canadien Inland Mariners in the Early Post-Conquest Era, 1760 to 1817 - More, John David (Université Queen's, 2021)
Keywords: Guerre; Navigation

1800 to 1830. Montréal, Building British Metropolis - Robert, Jean-Claude (Montréal Capital City. The Remarkable History of the Archaeological Site of St Anne’s Market and the Parliament of the Province of Canada, 2021)
Keywords: Métropole; Port

De 1800 à 1830. Montréal, jeune métropole britannique - Robert, Jean-Claude (Montréal capitale. L'exceptionnelle histoire du site archéologique du marché Sainte-Anne et du parlement de la province du Canada, 2021)
Keywords: Métropole; Port

Le canal de Lachine: un paysage en constant mouvement - Paradis, Matthieu; Gelly, Alain (Histoire Québec, 2020)
Keywords: Lachine (canal); Paysages

Histoire des communautés noires au Québec et à Montréal (2e partie) - Tessier, Stéphane (Il était une fois... Montréal-Nord, 2020)
Keywords: Chemins de fer; Musique; Noirs; Travail

Ponts et traverses de la rivière des Prairies - Tessier, Stéphane (Il était une fois... Montréal-Nord, 2020)
Keywords: Ponts; Rivière des Prairies; Rivière-des-Prairies

1840-1912: De la montée du Sault à la rue Lajeunesse: sept décennies de chemins de barrières... et quelques incendies - Lebleu, Jacques (Au fil d'ABC / SHAC, Société d'histoire d'Ahuntsic-Cartierville, 2019)
Keywords: Incendies; Routes; Rues

L'évolution des trains de banlieue montréalais: 170 ans de service (1847-2017) - Barrieau, Pierre (Université du Québec à Montréal, 2019)
Keywords: Chemins de fer; Gares; Transport en commun

En rade: marins à Montréal (1851-1896) - Bélisle-Desmeules, David (Domaine histoire, 2019)
Keywords: Navigation; Port; Travail; Vieux-port

Connaître et valoriser le patrimoine portuaire de Montréal: un chantier inachevé - Gelly, Alain (Histoire et patrimoine. Pistes de recherche et de mise en valeur, 2019)
Keywords: Histoire; Lachine (canal); Patrimoine; Port; Vieux-port

The years of dispersion - Fougères, Dany (Montreal: The History of A North American City, 2018)
Keywords: Côtes; Fortifications; Logement; Notre-Dame (paroisse); Routes; Rues; Villages

The Montreal Economy during the Nineteenth Century - Fougères, Dany; Labrecque, Annie-Claude (Montreal: The History of A North American City, 2018)
Keywords: Assurance; Banques; Chaussure; Chemins de fer; Lachine (canal); Montreal Board of Trade; Métropole; Port; Routes; Textile; Voie maritime

LAPORTE, sir HORMISDAS - Poitras, Claire (Dictionnaire biographique du Canada, 2018)

Le réseau ferroviaire du Canadien Pacifique à Montréal - Bur, Justin (Bulletin de l'Association québécoise pour le patrimoine industriel, 2017)
Keywords: Canadien Pacifique; Chemins de fer; Gare Viger; Gare Windsor; Gares

The Urban Horse and the Shaping of Montreal, 1840–1914 - Olson, Sherry (Animal Metropolis: Histories of Human-Animal Relations in Urban Canada, 2017)

Revealing new dynamics in the industrial city : a study of human/horse relations in Montreal's public space, 1860-1916 - Paulin, Catherine (Université de Montréal, 2017)
Keywords: Chevaux; Mont-Royal (parc)

Le Plateau sur ses grands chevaux (Bulletin de la Société d'histoire du Plateau-Mont-Royal, 2016)
Keywords: Chasse à courre; Chevaux; Clubs; Montreal Hunt Club; Tramways; Transport en commun

Au canal de Lachine - Desjardins, Pauline (Lumières sous la ville. Quand l'archéologie raconte Montréal, 2016)
Keywords: Lachine (canal); Navigation

Au Vieux-Port de Montréal - Desjardins, Pauline (Lumières sous la ville. Quand l'archéologie raconte Montréal, 2016)
Keywords: Port; Vieux-port

Georges-Étienne Cartier: le saint-patron des affairistes - Germain, Jean-Claude (Montréal en tête, 2016)
Keywords: Avocats; Cartier, Georges-Étienne; Chemins de fer; Grand Tronc

Urban Environments and the Animal Nuisance: Domestic Livestock Regulation in Nineteenth-Century Canadian Cities - Kheraj, Sean (Urban History Review / Revue d'histoire urbaine, 2015)

Au temps des chevaux et des rails (Bulletin de la Société d'histoire et de généalogie du Plateau-Mont-Royal, 2014)
Keywords: Automobile; Chemins de fer; Chevaux; Cyclisme; Funiculaire; Gares; Groupes populaires; Mont Royal; Plateau Mont-Royal; Quartiers; Tramways; Transport en commun

Montreal's First Railway - Leduc, Michael (Michael Leduc, 2013)
Keywords: Canadien Pacifique; Chemins de fer

Pointe-Saint-Charles: histoire de locomotives - Bélisle, Jean (Bulletin de l'Association québécoise pour le patrimoine industriel, 2012)
Keywords: Canadien National; Chemins de fer; Grand Tronc

Les années de dispersion - Fougères, Dany (Histoire de Montréal et de sa région, 2012)
Keywords: Côtes; Fortifications; Logement; Notre-Dame (paroisse); Routes; Rues; Villages

Une artère vitale: le fleuve - Gelly, Alain (Cap-aux-Diamants, 2012)
Keywords: Chemins de fer; Navigation; Routes

Relier Québec et Montréal par le chemin du Roy - Robichaud, Léon (Cap-aux-Diamants, 2012)
Keywords: Routes

Les Irlandais et le canal de Lachine. La grève de 1843 - Boily, Raymond (Leméac, 2011)
Keywords: Grèves; Irlandais; Lachine (canal)

Le pont du domaine Saint-Gabriel - Douaire, Gilles (Histoire Québec, 2011)
Keywords: Communautés religieuses; Lachine (canal); Ponts; Saint-Gabriel (ferme); Seigneurie; Sulpiciens; Séminaire

" Du chemin qui marche " au chemin du Roy à la Pointe-aux-Trembles - Desjardins, Pierre (Histoire Québec, 2010)
Keywords: Navigation; Pointe-aux-Trembles; Routes; Voirie

Le pont tubulaire et ferroviaire Victoria - Pratt, Michel (Histoire Québec, 2010)
Keywords: Chemins de fer; Ponts; Victoria (pont)

La compagnie maritime Allan: de l'Écosse au Canada au XIXe siècle - Blondel-Loisel, Annie (Là-bas, 2009)
Keywords: Allan Royal Mail Line; Allan, Andrew; Allan, Hugh; Navigation

WHA looks at some Prominent Westmounters (The Westmount Historian, 2008)
Keywords: Lait; Magasins; Port; Quartiers; Quincaillerie; Westmount

Montreal Railway Terminals - Leduc, Michael (Michael Leduc, 2008)
Keywords: Canadien National; Canadien Pacifique; Chemins de fer; Gares

Pointe St. Charles Shop - Leduc, Michael (Michael Leduc, 2007)
Keywords: Chemins de fer; Grand Tronc

L'organisation spatiale du corridor du canal de Lachine au XIXe siècle - Desjardins, Pauline (Association des archéologues du Québec, 2006)
Keywords: Lachine (canal)

Voies pointelières d'hier et d'aujourd'hui - Desjardins, Pierre (Atelier d'histoire de Pointe-aux-Trembles, 2006)
Keywords: Chemins de fer; Navigation; Pointe-aux-Trembles; Quartiers

94 ans après la Conquête un premier navire français à Montréal - Gaudet, Sylvain (Montréal en tête, 2006)
Keywords: Commerce de détail; Marchands; Port

KENNEDY, sir JOHN - Millard, J. Rodney (Dictionnaire biographique du Canada, 2005)

STEPHEN, GEORGE, 1er baron Mount Stephen - Reford, Alexander (Dictionnaire biographique du Canada, 2005)

SHAUGHNESSY, THOMAS GEORGE, 1er baron SHAUGHNESSY - Regehr, Theodore D. (Dictionnaire biographique du Canada, 2005)

ROSS, WILLIAM GILLIES - Ross, W. Gillies (Dictionnaire biographique du Canada, 2005)

Muddy Shore to Modern Port: Redimensioning the Montréal Waterfront Time-Space - Gilliland, Jason A. (The Canadian Geographer / Le Géographe canadien, 2004)
Keywords: Paysages; Port

Navigation and Waterpower : Adaptation and Technology on Canadian Canals - Desjardins, Pauline (The Journal of the Society for Industrial Archeology, 2003)
Keywords: Navigation; Énergie hydraulique

Behind the Scene of the Lachine Canal Landscape - Desloges, Yvon (The Journal of the Society for Industrial Archeology, 2003)
Keywords: Lachine (canal)

A Precipitous Decline, Steam as a Motive Power in Montreal : A Case Study of the Lachine Canal Industries - Gelly, Alain (The Journal of the Society for Industrial Archeology, 2003)
Keywords: Lachine (canal); Énergie hydraulique

Steam or Water Power? Thomas C. Keefer and the Engineers Discuss the Montreal Waterworks in 1852 - Ross, Susan M. (The Journal of the Society for Industrial Archeology, 2003)
Keywords: Aqueduc; Énergie hydraulique

CATELLI, CARLO ONORATO (Charles-Honoré) - Scardellato, Gabriele (Dictionnaire biographique du Canada, 2003)

Le canal de Lachine: l’eau à l’œuvre - Desloges, Yvon (Continuité, 2002)
Keywords: Lachine (canal)

La rivière des Prairies - Dupont, Antonin (Il était une fois... Montréal-Nord, 2002)
Keywords: Navigation; Rivière des Prairies

Programme d'inventaire archéologique de la Pointe-des-Seigneurs - Société d'archéomatique Chronogramme-Lauverbec (Société d'archéomatique Chronogramme-Lauverbec, 2002)
Keywords: Artisans; Confection; Fer et acier; Lachine (canal); Meunerie; Mouleurs; Ogilvie Flour Mills; Énergie hydraulique

Le Saint-Laurent, comme une rue principale - Franck, Alain (Continuité, 2001)
Keywords: Navigation; Voie maritime

Redimensioning Montreal: Circulation and Urban Form, 1846-1918 - Gilliland, Jason A. (Université McGill, 2001)
Keywords: Incendies; Port; Rues

Le chemin de fer sur la glace - Lefort, Pierre (Histoire Québec, 2000)
Keywords: Canadien Pacifique; Chemins de fer; Longueuil; Ponts; Victoria (pont)

Steamboat connections : Montreal to Upper Canada, 1816-1843 - Mackey, Frank (McGill-Queen's University Press, 2000)
"In Steamboat Connections Frank Mackey gives us a narrative account of the first twenty-five years of steam navigation along the St. Lawrence and Ottawa Rivers. Relying on a wealth of primary archival sources, Mackey focuses on the development of steamer traffic from 1816 - when the foundations were laid for the first stage and steamboat line between Montreal and Upper Canada - to the early 1840s - when locks, canals, innovations, and human daring conquered the rapids on those rivers and allowed for navigation between Montreal and the Great Lakes. He shows how, starting in 1841, small steamers ran "the circuit" - down the rapids of the St. Lawrence to Montreal and then back up to Kingston and other Great Lakes ports via the Ottawa River and the Rideau Canal." "Mackey introduces the entrepreneurs who forged this important link between Montreal and the nation's interior and chronicles the course of their industry, correcting previous misinterpretations. He sheds light not only on steamboats but also on the social, commercial, and geographical development they made possible. He shows that the history of this country, a land with vast expanses and a harsh climate, cannot be fully appreciated without looking at the different modes of transportation that made it possible."--BOOK JACKET.
Keywords: Navigation